The national helpdesk activity in Italy: report of the first year (2010) - Ludovica Malaguti Aliberti; Paolo Izzo (Istituto Superiore di Sanità, 2011)
National CLP heldpesk is a service established in every Member State providing advice to companies and other stakeholders on the obligations they may have under CLP. In Italy the national helpdesk is located into the Center of Chemical Substances (CSC) in the National Institute of Health. Helpdesks will provide with wide ranging information on the provisions of CLP. They will also advice on the responsibilities the suppliers of chemical substances have to fulfill under these Regulations. Too specific questions cannot be answered as the aim of the helpdesk is to give a general interpretation of CLP principles and requirements instead of solving tailor made problems.